ANALISIS FITOKIMIA DAN TOKSISITAS (BRINE SHRIMP LETHALITY TEST) EKSTRAK SERBUK SARI DARI Trigona incisa - Novalien Fiergiyanti; Erwin -; Syafrizal - (JURNAL KIMIA MULAWARMAN, 2015)
The phytochemical, brine shrimp lethality and activity antioxidant test and secondary metabolits of bee pollen have been conducted. The pollen samples are extract with solvent ethanol by masseration method and that is concentrated by using rotary evaporator. The ethanol crude extract obtained are fractioned with solvent ethanol and solvent ethyl acetat. Based on secondary metabolits phytochemical test of bee pollen showed that ethanol crude extract contains alkaloid and fenolik. Ethanol fraction extract contains alkaloid. Ethyl acetat fraction extract contains alkaloid and fenolik. In brine shrimp lethality test, the increase larvae (Artemia salina L.) death and data was yielded recorded then processed using SAS Probit Analysis to determine the lethal concentration 50% (LC50) value. The results of this test obtained data and showed that the most active fraction is ethanol fraction extract with value of LC50 was equel to 249,60 ppm.Keywords: Bee pollen, phytochemical test, brine shrimp lethality test (BSLT).